CliffEBM - A Gridded Ice Cliff Energy Balance Model (first public release, v01.1) - Buri, Pascal; Steiner, Jakob F.; Miles, Evan S.; Immerzeel, Walter W.; Pellicciotti, Francesca (Zenodo, 2023)
CliffEBM is a model that calculates the distributed surface energy balance and backwasting (melt) rates for ice cliffs, i.e. steep ice surfaces with complex, heterogeneous topographies.The model is validated and described in Buri, P., Pellicciotti, F., Steiner, J., Miles, E., & Immerzeel, W. (2016). A grid-based model of backwasting of supraglacial ice cliffs on debris-covered glaciers. Annals of Glaciology, 57 (71), 199-211. https://doi.org/10.3189/2016AoG71A059 See most update version here: https://github.com/pburi/CliffEBM In this repository we provide example input data (digital elevation models, shapefiles, meteodata) to run CliffEBM on one supraglacial cliff on the debris-covered Lirung Glacier (Nepal). Working example: to run the model, download the entire repository on your machineand adjust the paths in the model code ( CliffEBM.R , section " primary definitions ") according to the paths on your machine. Software: R (R version 4.3.0 (2023-04-21 ucrt) -- "Already Tomorrow"). The model should also run on older versions. Packages: cleaRskyQuantileRegression , doParallel, foreach, grDevices, iterators, methods, parallel, raster, rgdal, rgeos, sf, sp, stats, utils, zoo This study was funded by the SNF (Swiss National Science Foundation) project UNCOMUN ("Understanding Contrasts in High Mountain Hydrology in Asia," Grant No. 146761).